Pattern of Road Traffic Crashes in Sri Lanka from 2006 to 2009 - DA Gunawardane; SD Dharmaratne (College of Community Physicians of Sri Lanka, 2013)
DOI: http://dx.doi.org/10.4038/jccpsl.v18i1.6079 Journal of the College of Community Physicians of Sri Lanka Vol.18(1) June 2013 33-34